FORMULASI, KARAKTERISASI DAN UJI PENETRASI IN VITRO PATCH EKSTRAK BIJI KOPI ROBUSTA (COFFEA CANEPHORA) SEBAGAI SEDIAAN ANTI SELULIT - Isriany Ismail; Surya Ningsi; Naswina Putrianti (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Cellulite is a very common topographical alteration in which the skin acquires an "orange peel". Caffeine is the classification which can be used as an anti-cellulite in patch. The basic material used is Robusta coffee bean extract (Coffea canephora), which has a high caffeine content. This study aimed to knowing how much Chitosan polymer and HPMC ratio which can produce a patch with the characteristics and good penetration and show its releasing profile. Patch madewith chitosan concentrations : HPMC1:1 (formula I), 2:1 (formula II), and 1: 2 (formula III) by increasing in glycerin as plastizier and Tween 80, penetration enhancers used solvent casting method. The penetration ability was tested as in vitro by Franz diffusion instrument modified in using the human cadaver skin. Penetration test performed for two hours with sampling in the minute, 5 10, 15, 45, 60, 90 and 120. Each sampling measured on UV-Vis spectrophotometer. The results obtained were the three formulasy characteristics of a good patch with the varying releasing profiles. Formula I and II showed the Higuchi’s releasing profile, while the formula III showed zero-order releasing profile.